Stable Consciousness? The “Hard Problem” Historically Reconstructed and in Perspective of Neurophenomenological Research on Meditation - Schleim, Stephan (Frontiers in Psychology, 2022)
Finding a scientific, third-person explanation of subjective experience or phenomenal content is commonly called the “hard problem” of consciousness. There has recently been a surge in neuropsychological research on meditation in general and long-term meditators in particular. These experimental subjects are allegedly capable of generating a stable state of consciousness over a prolonged period of time, which makes experimentation with them an interesting paradigm for consciousness research. This perspective article starts out with a historical reconstruction of the “hard problem”, tracing it back to Gottfried Wilhelm Leibniz and Emil du Bois-Reymond in the 18th and 19th century, respectively, and the problem of introspection as already acknowledged by Wilhelm Wundt in the 19th century. It then discusses the prospects of research on long-term meditators from a contemporary perspective and with respect to the neurophenomenological research program already advocated by Francisco J. Varela.